PERSEPSI DAN MOTIVASI WISATAWAN STAYCATION BERKUNJUNG KE DESA BATUR KINTAMANI DI MASA PANDEMI COVID-19 - Adi Palguna, I Kadek; Wijaya, NMS.; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
Staycation become more of trend during the pandemic COVID, because it does not require a lot of time, money and near home. The purpose of this study was to determine the characteristics, perceptions and motivations of staycation tourist visiting the Batur Kintamani Village during the pandemic COVID-19. The sample in this study were staycation tourist in the Batur Kintamani Village during the pandemic COVID-19. The sampling technique used purposive sampling on 100 respondents. The data collection technique by: observation, interview, questionnaire and literature study. The data analysis technique used in this research is qualitatif descriptive analysis. The results of the study indicate that the characteristics of tourists are dominated by tourists aged between 21 to 30 years old, gender are dominated by female, profession are dominated by students or university students. The perception of staycation tourists getting an average attitude of agree which dominated by factor of the Batur Kintamani Village as a favorite place to take pictures. In staycation tourist motivation, push factor dominated by factor of wanting to relax or refresh during the pandemic COVID-19 and pull factor dominated by factor the beautiful view of mountain and lake are interesting to take pictures. Push factor get a higher average score than pull factor, so that the push factor becomes the dominant factor affecting staycation tourist motivation come to the Batur Kintamani Village during the pandemic COVID-19